Baroque Ensemble- Fall Quarter Recital December 7, 2015 - Baroque Ensemble; Terry, Carole; Prendergast, Chloe; Pokorny, Corentin; Franz, Gwen; Myklebust, Sonja; van de Burgt, Stephen; Chalasani, Vijay; Smith, Wyatt; Keuhn, Jonathan (University of Washington School of Music, 2015)
Baroque Ensemble- Fall Quarter Recital December 7, 2015
Concert Program